2020
DOI: 10.3390/medicina56110573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the CB1 Receptor Antagonists AM6545 and AM4113 on Insulin Resistance in a High-Fructose High-Salt Rat Model of Metabolic Syndrome

Abstract: Background and Objectives: Insulin resistance (IR) is a serious condition leading to development of diabetes and cardiovascular complications. Hyper-activation of cannabinoid receptors-1 (CB1) has been linked to the development of metabolic disorders such as IR. Therefore, the effect of blocking CB1 on the development of IR was investigated in the present study. Materials and Methods: A 12-week high-fructose/high-salt feeding model of metabolic syndrome was used to induce IR in male Wistar rats. For this purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…The increased risk of developing kidney disease in MetS has been well documented [ 6 , 7 , 8 ]. We have recently demonstrated that eight weeks of high-fructose and high-salt loading in Wistar rats was sufficient to induce a state of MetS manifested by obesity, hyperinsulinemia, hyperuricemia and dyslipidemia [ 28 ]. Furthermore, we have demonstrated that pre-treatment of these animals with either AM6545 or AM4113 caused an alleviation of the developed metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The increased risk of developing kidney disease in MetS has been well documented [ 6 , 7 , 8 ]. We have recently demonstrated that eight weeks of high-fructose and high-salt loading in Wistar rats was sufficient to induce a state of MetS manifested by obesity, hyperinsulinemia, hyperuricemia and dyslipidemia [ 28 ]. Furthermore, we have demonstrated that pre-treatment of these animals with either AM6545 or AM4113 caused an alleviation of the developed metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that the area under the curve of the oral glucose tolerance test following an oral challenge of glucose was higher in the metabolic syndrome group relative to the controls. Effects on blood glucose levels were ameliorated after either AM6545 or AM4113 administration [ 28 ]. Moreover, studies by members of our group have shown that both AM6545 and AM4113 reduce food intake in rodents and thus can be useful in the treatment of obesity [ 22 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations